2020
DOI: 10.5194/acp-20-865-2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct diurnal variation in organic aerosol hygroscopicity and its relationship with oxygenated organic aerosol

Abstract: Abstract. The hygroscopicity of organic aerosol (OA) is important for investigation of its climatic and environmental impacts. However, the hygroscopicity parameter κOA remains poorly characterized, especially in the relatively polluted environment on the North China Plain (NCP). Here we conducted simultaneous wintertime measurements of bulk aerosol chemical compositions of PM2.5 and PM1 and bulk aerosol hygroscopicity of PM10 and PM1 on the NCP using a capture-vaporizer time-of-flight aerosol chemical speciat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 51 publications
8
64
0
Order By: Relevance
“…One explanation is that f 60 depends on biomass fuels, burning conditions (e.g., flaming or smoldering), and also chemical aging (Hennigan et al, 2011;Schneider et al, 2006;Collier et al, 2016). In addition, we also observed relatively high fractions of C x H y N + z in BBOA (4.2 %-10.2 %) and high N/C ratios (0.014-0.039), consistent with the observations of abundant nitrogen-containing organic compounds, e.g., N-heterocyclic alkaloid compounds, amines, and nitrated phenols from biomass burning (Reyes-Villegas et al, 2018b;Bottenus et al, 2018;Wang et al, 2017;Laskin et al, 2009;Desyaterik et al, 2013). Compared with SV-AMS, the BBOA spectra of CV-ACSM are overall similar (R 2 = 0.93-0.96, Fig.…”
Section: Crop Straw Burningsupporting
confidence: 87%
“…One explanation is that f 60 depends on biomass fuels, burning conditions (e.g., flaming or smoldering), and also chemical aging (Hennigan et al, 2011;Schneider et al, 2006;Collier et al, 2016). In addition, we also observed relatively high fractions of C x H y N + z in BBOA (4.2 %-10.2 %) and high N/C ratios (0.014-0.039), consistent with the observations of abundant nitrogen-containing organic compounds, e.g., N-heterocyclic alkaloid compounds, amines, and nitrated phenols from biomass burning (Reyes-Villegas et al, 2018b;Bottenus et al, 2018;Wang et al, 2017;Laskin et al, 2009;Desyaterik et al, 2013). Compared with SV-AMS, the BBOA spectra of CV-ACSM are overall similar (R 2 = 0.93-0.96, Fig.…”
Section: Crop Straw Burningsupporting
confidence: 87%
“…The correlation pattern of another monoterpene SOA tracer, cis-pinonic acid, was different from that of 3-hydroxyglutaric acid. Chamber studies showed that cis-pinonic acid could be produced through gas-phase reactions of monoterpenes (Yu et al, 1999;Larsen et al, 2001), which significantly contributed to the newly nucleated particles (Zhang et al, 2012). Previous field observations also found that cis-pinonic acid was closely associated with the nucleation processes in the first step of the SOA formation from organic vapors (Alier et al 2013;van Drooge et al, 2018).…”
Section: Influencing Factors For the Formation Of Different Soa Tracersmentioning
confidence: 94%
“…A variety of instruments have been developed to measure CCN number concentrations (Twomey, 1963;Sinnarwalla and Alofs, 1973;Fukuta and Saxena, 1979;Hudson, 1989;Ji et al, 1998;Chuang et al, 2000;McMurry, 2000;Nenes et al, 2001;Otto et al, 2002;VanReken et al, 2004;Roberts and Nenes, 2005;Frank et al, 2007;Kreidenweis and Asa-Awuku, 2014). Currently, the most widely used one is the continuous-flow streamwise thermal gradient CCN counter based on the design of Roberts and Nenes (2005) and Lance et al (2006) and commercialized by Droplet Measurement Technologies. Mode details of this instrument can be found elsewhere (Roberts and Nenes, 2005;Lance et al, 2006).…”
Section: Ccn Activitiesmentioning
confidence: 99%
“…Currently, the most widely used one is the continuous-flow streamwise thermal gradient CCN counter based on the design of Roberts and Nenes (2005) and Lance et al (2006) and commercialized by Droplet Measurement Technologies. Mode details of this instrument can be found elsewhere (Roberts and Nenes, 2005;Lance et al, 2006).…”
Section: Ccn Activitiesmentioning
confidence: 99%
See 1 more Smart Citation